Clonal evolution detected with conventional cytogenetic analysis is a potent prognostic factor in adult patients with relapsed Philadelphia chromosome-negative acute lymphoblastic leukemia. (April 2021) - Shimizu, Hiroaki; Yokohama, Akihiko; Ishizaki, Takuma; Hatsumi, Nahoko; Takada, Satoru; Saitoh, Takayuki; Sakura, Toru; Handa, Hiroshi
Highlights: Half of Ph-negative ALL patients acquired additional cytogenetic abnormalities (ACA). Patients with ACA acquisition showed the significantly inferior survival rate. Allogeneic transplant could not conquer this dismal subset of Ph-negative ALL. Abstract: Additional cytogenetic abnormality (ACA) acquisition at relapse has been recognized as clonal evolution at the cytogenetic level, and has a significant prognostic impact on relapsed acute myeloid leukemia (AML) patients. We retrospectively investigated 48 relapsed Philadelphia chromosome (Ph)-negative acute lymphoblastic leukemia (ALL) patients to clarify the clinical significance of ACA acquisition at the first relapse. Twenty-seven patients (56 %) acquired ACA at the first relapse. No significant predisposing factor for ACA acquisition was identified. Notably, patients with ACA acquisition showed a significantly lower second complete remission rate compared to those without ACA acquisition (14.8 % vs. 76.2 %, respectively; p < 0.01), and furthermore, the overall survival rates after the first relapse were significantly different between patients with and without ACA acquisition (25.9 % vs. 55.3 % at 1 year, respectively; p < 0.01). Multivariate analysis extracted ACA acquisition as the only negative prognostic factor (hazard ratio: 2.55, p < 0.01). All seven patients with ACA acquisition who underwent allogeneic transplant died within 2 years after relapse. These findings suggested that clonal evolution detected with conventional cytogenetic analysis at the first relapse triggers severe chemo-refractoriness in Ph-negative ALL cells, just like AML cells. Novel therapeutic strategies are warranted for this subset of patients.